THE ROLE OF PEACEKEEPERS IN ENSURING INTERNATIONAL COLLECTIVE SECURITY - Kvasniy , L.G.; Paslavska , V.V.; Basarab , O. V. (The actual problems of regional economy development, 2022)
The article argues that the task of preserving peace, preventing armed conflict, and preventing the destruction of people during military and ethnic conflicts requires the combined efforts of the world community. The issue of the role of UN peacekeeping activities, participation of individual states in it, including Ukraine, is considered. It has been proven that the war in Ukraine, caused by Russia's military aggression, has shown that the world has not become stable, as conflicts are erupting in many countries, as in previous years. The current war in Ukraine, caused by Russia, has shown the inadequacy and ineffectiveness of UN support for ending the war and ensuring international security. It has been established that, historically, NATO's main role has been to ensure the freedom and security of its member countries through political and military means. NATO adheres to the values ​​of democracy, individual freedom, the rule of law and the peaceful settlement of disputes. World experience shows that neutrality today is economically, politically and securely disadvantageous. It is substantiated that new unforeseen threats and security challenges pose a problem of choice for every civilized country: military neutrality or participation in the system of collective security. Joint action is needed against a common threat. The nature of the threat has changed, the means to combat it have changed - too, but the principle has remained the same - the collective defense of countries united by common values. Emphasis is placed on the fact that today Ukrainians are learning a lesson: peace agreements signed by governments that participate in or encourage mass violations of human rights have no value and cannot be implemented in practice. It has been proved that in such a situation it is not expedient to maintain peace by mutual consent, it must be resolved by joint action. In the course of the research the authors used the methods of historical approach, comparison, theoretical generalization of description, concretization, formalization, formation of proposals, providing conclusions and generalizations.